2014
DOI: 10.4269/ajtmh.13-0455
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Patterns of Ross River Virus Disease in Queensland, Australia, 2001–2011

Abstract: Ross River virus (RRV) infection is a debilitating disease that has a significant impact on population health, economic productivity, and tourism in Australia. This study examined epidemiologic patterns of RRV disease in Queensland, Australia, during January 2001–December 2011 at a statistical local area level. Spatio-temporal analyses were used to identify the patterns of the disease distribution over time stratified by age, sex, and space. The results show that the mean annual incidence was 54 per 100,000 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…14 In the only study conducted among blood donors, seroprevalence for RRV antibodies was 8.4% from the 2,952 sera collected in South Australia in 1992. 29 To our knowledge, except for Australia where RRV is the most common and widespread arboviral disease with about 5,000 cases notified annually, 11,30 and to a lesser extent for Fiji, 16,24 there are no recent data about circulation of RRV in the Pacific area.…”
Section: S U M M a R Ymentioning
confidence: 96%
“…14 In the only study conducted among blood donors, seroprevalence for RRV antibodies was 8.4% from the 2,952 sera collected in South Australia in 1992. 29 To our knowledge, except for Australia where RRV is the most common and widespread arboviral disease with about 5,000 cases notified annually, 11,30 and to a lesser extent for Fiji, 16,24 there are no recent data about circulation of RRV in the Pacific area.…”
Section: S U M M a R Ymentioning
confidence: 96%
“…Fortunately, infected patients are usually asymptomatic and recover without giving rise to any observable clinical outcomes . However, disease severity in symptomatic patients during the prodromal and acute phases, as well as the frequency of central nervous system involvement, mortality rates and permanent neurological complications in survivors, are disproportionately higher in children and the elderly . During the natural aging process from infancy to old age in humans, the host immune system undergoes a subtle yet progressive change – immunosenescence .…”
Section: Manifestations Of Infectionmentioning
confidence: 99%
“…34,36 However, disease severity in symptomatic patients during the prodromal and acute phases, as well as the frequency of central nervous system involvement, mortality rates and permanent neurological complications in survivors, are disproportionately higher in children and the elderly. 6,[37][38][39][40] During the natural aging process from infancy to old age in humans, the host immune system undergoes a subtle yet progressive changeimmunosenescence. 41,42 Although many studies have identified the possible effects of aging on the immune system, few have associated these effects with alphavirus disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Because RRV has seasonal variability, samples were collected during "higher risk" months. The month of March appeared to have higher rates of RRV in the Northern Territory and Queensland, 27,28 and this was confirmed by notification data demonstrating a notification peak in March (data available from: http://www9. health.gov.au/cda/source/rpt_3.cfm); therefore, collections commenced during this month for all donor centers ( Fig.…”
Section: Methodsmentioning
confidence: 60%